The Potential for Immersive Technology combined with Online Dating - Bailey, David Evans (Journal of Telecommunications and the Digital Economy, 2017)
Whilst online dating has been around for several years; immersive technologies are relatively new to this type of interaction. The first forays into immersive VR online dating have only just being made in the past year. To what degree this type of technology will change the way that we date is potentially quite different from the current way that online dates are conducted. The way the technology works could make virtual dates seem as real as a physical date. Understanding how immersive technology functions gives some insights into the future of online dating and also the impact on the digital economy.